Answer:
2 and 4
Step-by-step explanation:
2+4 = 6
6/2 = 3
average is sum of number divided by how many numbers there are.
Answer:
A. (x + 2)^2 = 31.
Step-by-step explanation:
x^2 + 4x = 27
x^2 + 4x - 27 = 0
A. (x + 2)^2 = 31
x^2 + 4x + 4 - 31 = 0
x^2 + 4x - 27 = 0
This option corresponds to the given equation, so it is correct.
B. (x + 2)^2 = 43
x^2 + 4x + 4 - 43 = 0
x^2 + 4x - 39 = 0
This does not correspond to the equation.
C. (x + 4)^2 = 31
x^2 + 8x + 16 - 31 = 0
x^2 + 8x - 15 = 0
This does not correspond to the equation.
D. (x+4)^2 = 43
x^2 + 8x + 16 - 43 = 0
x^2 + 8x - 27 = 0
This does not correspond to the equation.
So, your answer is A. (x + 2)^2 = 31.
Make sure to SUBMIT and check your PREVIOUS answers to make sure they are right! XD Also, hope this helps!
Answer:
Step-by-step explanation:
ok, so this is an infinitly repeating function, so you can write it as:
sqrt(12-x)
Although, x is also equal to sqrt(12-x), so
x = sqrt(12-x), and
x^2 = 12-x
x^2-12+x = 0
now just apply the quadratic formula and you're good
hope i helped :D
To determine the nth term, we must create a function.
f(n) = 1st term + common difference (n - 1)
n = term you are looking for
1st term = 1st number in the sequence
common difference = the difference between two consecutive numbers in the sequence.
based on the above sequence, the 1st term is 2, its common difference is 3.
f(n) = 2 + 3(n-1)
Assuming we are looking for the 5th term
f(5) = 2 + 3(5-1)
= 2 + 3(4)
= 2 + 12
f(5) = 14 as you can see in the above sequence 14 is the 5th term.
For any other value of the nth term, simply substitute n by the number of the term and solve the equation.
Replace X with 3 and simplify. The answer you would get is 11.